Different folding mechanisms in prion proteins from mammals with different disease susceptibility observed at the single-molecule level - Uttam Anand; Shubhadeep Patra; Rohith Vedhthaanth Sekar; Craig R. Garen; Michael T. Woodside (Proceedings of the National Academy of Sciences, 2025)
Misfolding of the protein PrP causes prion diseases in mammals. Disease susceptibility varies widely among species, despite PrP sequences differing by only a few amino acids. How these differences alter PrP folding and misfolding remains unclear. We compared the folding dynamics of single PrP molecules from three species with different disease susceptibility: dogs (immune), hamsters (susceptible), and bank voles (extremely susceptible). Measurements with optical tweezers revealed important differences between the folding cooperativity, pathways, energy barriers, and kinetics of these proteins. In contrast to the two-state folding of hamster PrP, dog PrP always folded through multiple intermediates. However, both featured rapid native folding, homogeneous energy barriers, and no readily observable misfolding. Bank vole PrP also folded via intermediates, but more slowly and via inhomogeneous barriers. Most notably, it formed several metastable misfolded states starting from the unfolded state. Analyzing the sequence of intermediates seen in pulling curves, we found significant differences in the folding pathways for dog and bank vole PrP, implying that sequence mutations altered energy barriers so as to redirect folding pathways. These results show that subtle differences in PrP sequence between species produce profound changes in folding behavior, providing insight into the factors underlying misfolding propensity.